Covalent Triazine Framework Nanoparticles via Size‐Controllable Confinement Synthesis for Enhanced Visible‐Light Photoredox Catalysis. Issue 42 (21st September 2020) - Huang, Wei; Huber, Niklas; Jiang, Shuai; Landfester, Katharina; Zhang, Kai A. I.
Abstract: For metal‐free, organic conjugated polymer‐based photocatalysts, synthesis of defined nanostructures is still highly challenging. Here, we report the formation of covalent triazine framework (CTF) nanoparticles via a size‐controllable confined polymerization strategy. The uniform CTF nanoparticles exhibited significantly enhanced activity in the photocatalytic formation of dibenzofurans compared to the irregular bulk material. The optoelectronic properties of the nanometer‐sized CTFs could be easily tuned by copolymerizing small amounts of benzothiadiazole into the conjugated molecular network. This optimization of electronic properties led to a further increase in observed photocatalytic efficiency, resulting in total an 18‐fold enhancement compared to the bulk material. Full recyclability of the heterogeneous photocatalysts as well as catalytic activity in dehalogenation, hydroxylation and benzoimidazole formation reactions demonstrated the utility of the designed materials. Abstract : Size‐controllable covalent triazine framework nanoparticles were synthesized through a confined polymerization strategy within silica capsules. They show a manifold increase in photocatalytic activity compared to the bulk system.